Sustainable Management of Islamic Education - Wajdi, Muh Barid Nizarudin; Marlina, Yuli; Ansori, Ansori; Irsyadiah, Nur (Proceedings of Annual Conference for Muslim Scholars, 2024)
This study presents a comprehensive bibliometric analysis of sustainable management in Islamic education, covering publications from 1994 to 2024. Utilizing data solely from the Scopus database, the research identifies key trends, contributors, and emerging themes within the field. A total of 58 documents were analyzed, focusing on their thematic content, publication frequency, and institutional affiliations. The findings reveal a significant increase in scholarly attention towards sustainable management in Islamic education, particularly in Southeast Asia, with institutions such as Emirates College for Advanced Education and Universiti Utara Malaysia leading the contributions. The study underscores the importance of integrating sustainability practices into Islamic educational frameworks and highlights areas requiring further research, including economic implications and innovation. The analysis offers valuable insights for scholars and practitioners aiming to enhance the sustainability of Islamic education in response to global challenges.